The impacts of Japan's negative interest rate policy on Asian financial markets - Shin-ichi Fukuda (Asian Development Bank Institute (ADBI), 2017)
The purpose of this paper is to explore the spillover effects Japan's negative interest rate policy (NIRP) had on Asian financial markets. Unlike the quantitative and qualitative monetary easing (QQE) without a negative interest rate, the NIRP not only had limited impacts on Japan's economy but also raised a serious concern about profitability of local financial institutions. It is thus likely that its spillover effects are very different from those of the QQE without a negative interest rate. In the analysis, we examine spillover effects on Asian stock markets. We find that Japan's long-term interest rate had significant negative effects on Asian stock prices during the NIRP period. We also find that the spillover effects were especially significant through a decline of excess returns in Japan's finance sector. The results imply that the NIRP that lowered the long-term rate below zero might have benefited Asian economies. We discuss that this might have happened because local financial institutions who lost their profit opportunities in domestic markets explored a new profit opportunity in emerging Asia after the NIRP was announced.
Keywords: F10; F32; E52; 330; negative interest rate; international spillover; emerging economies; stock markets in Asia; financial institutions